Hippo vs. Crab: tissue‐specific functions of the mammalian Hippo pathway. (January 2017) - Nishio, Miki; Maehama, Tomohiko; Goto, Hiroki; Nakatani, Keisuke; Kato, Wakako; Omori, Hirofumi; Miyachi, Yosuke; Togashi, Hideru; Shimono, Yohei; Suzuki, Akira
Abstract : The Hippo signaling pathway is a vital suppressor of tumorigenesis that is often inactivated in human cancers. In normal cells, the Hippo pathway is triggered by external forces such as cell crowding, or changes to the extracellular matrix or cell polarity. Once activated, Hippo signaling down‐regulates transcription supported by the paralogous cofactors YAP1 and TAZ. The Hippo pathway's functions in normal and cancer biology have been dissected by studies of mutant mice with null or conditional tissue‐specific mutations of Hippo signaling elements. In this review, we attempt to systematically summarize results that have been gleaned from detailed in vivo characterizations of these mutants. Our goal is to describe the physiological roles of Hippo signaling in several normal organ systems, as well as to emphasize how disruption of the Hippo pathway, and particularly hyperactivation of YAP1/TAZ, can be oncogenic. Abstract : The Hippo pathway, which is triggered by external forces such as cell crowding, or changes to the extracellular matrix or cell polarity, and particular growth factors, is a vital suppressor of tumorigenesis and often inactivated in human cancers. In this review, we attempt to systematically summarize the phenotypes of conditionally gene‐targeted mice bearing tissue‐specific mutations of Hippo signaling components. These findings should advance the generation of new, more effective, targeted anti‐cancer therapies.